Selenite Uptake and Transformation in Rice Seedlings (Oryza sativa L.): Response to Phosphorus Nutrient Status - Wang, Yaqi; Wang, Kang; Wang, Qi; Wan, Yanan; Zhuang, Zhong; Yu, Yao; Li, Huafen (Frontiers in Plant Science, 2020)
Selenite and phosphate share similar uptake mechanisms, as a phosphate transporter is involved in the selenite uptake process. However, the mechanism by which selenium (Se) transformation in plants is mediated by phosphorus (P) remains unclear. In this hydroponic study, the absorption, translocation, and biotransformation of Se in selenite-treated rice (Oryza sativa L.) seedlings were investigated under varying P nutrient status. The results showed that P-deficient cultivation increased the Se concentration in roots with Se-only treatment by 2.1 times relative to that of the P-normal condition. However, co-treating roots with additional P caused the Se concentration to decline by 20% and 73% compared to Se treatment alone under P-normal and P-deficient cultivation, respectively. A similar pattern was also observed in Se uptake by rice roots. With an Se-transfer factor elevated by 4.4 times, the shoot Se concentration was increased by 44% with additional P supply compared to the concentration under Se-only treatment of P deficiency; however, no significant differences were observed regarding P-normal cultivation. P deficiency increased the Se percentage by 28% within the cell wall, but reduced it by 60% in the soluble fraction of Se-only treated roots relative to that of the P-normal condition. Contrarily, compared with the Se-only treatment under P deficiency, additional P supply enhanced Se storage in the root soluble fraction by 1.3 times. The opposite tendency was observed for rice shoots. Moreover, P deficiency reduced the proportion of SeMet by 22%, but increased MeSeCys by 1.3 times in Se-only treated roots compared to those under the P-normal condition. Interestingly, MeSeCys was not detected when additional P was added to the two cultivation conditions. Unlike in the roots, only SeMet was generally detected in the rice shoots. The results demonstrate that the P nutrient status strongly affects the Se biofortification efficiency in rice seedlings by altering the Se subcellular distribution and speciation.